Understanding and improving experiences of care in hospital for people living with dementia, their carers and staff: three systematic reviews - Ruth Gwernan-Jones; Ilianna Lourida; Rebecca A Abbott; Morwenna Rogers; Colin Green; Susan Ball; Anthony Hemsley; Debbie Cheeseman; Linda Clare; Darren Moore; Julia Burton; Sue Lawrence; et al. (National Institute for Health Research, 2020)
Background: Being in hospital can be particularly confusing and challenging not only for people living with dementia, but also for their carers and the staff who care for them. Improving the experience of care for people living with dementia in hospital has been recognised as a priority. Objectives: To understand the experience of care in hospital for people living with dementia, their carers and the staff who care for them and to assess what we know about improving the experience of care. Review methods: We undertook three systematic reviews: (1) the experience of care in hospital, (2) the experience of interventions to improve care in hospital and (3) the effectiveness and cost-effectiveness of interventions to improve the experience of care. Reviews 1 and 2 sought primary qualitative studies and were analysed using meta-ethnography. Review 3 sought comparative studies and economic evaluations of interventions to improve experience of care. An interweaving approach to overarching synthesis was used to integrate the findings across the reviews. Data sources: Sixteen electronic databases were searched. Forwards and backwards citation chasing, author contact and grey literature searches were undertaken. Screening of title and abstracts and full texts was performed by two reviewers independently. A quality appraisal of all included studies was undertaken. Results: Sixty-three studies (reported in 82 papers) were included in review 1, 14 studies (reported in 16 papers) were included in review 2, and 25 studies (reported in 26 papers) were included in review 3. A synthesis of review 1 studies found that when staff were delivering more person-centred care, people living with dementia, carers and staff all experienced this as better care. The line of argument, which represents the conceptual findings as a whole, was that 'a change of hospital culture is needed before person-centred care can become routine'. From reviews 2 and 3, there was some evidence of improvements in experience of care from activities, staff training, added capacity and inclusion of carers. In consultation with internal and external stakeholders, the findings from the three reviews and overarching synthesis were developed into 12 DEMENTIA CARE pointers for service change: key institutional and environmental practices and processes that could help improve experience of care for people living with dementia in hospital. Limitations: Few of the studies explored experience from the perspectives of people living with dementia. The measurement of experience of care across the studies was not consistent. Methodological variability and the small number of intervention studies limited the ability to draw conclusions on effectiveness. Conclusions: The evidence suggests that, to improve the experience of care in hospital for people living with dementia, a transformation of organisational and ward cultures is needed that supports person-centred care and values the status of dementia care. Changes need to cut across hierarchies and training systems to facilitate working patterns and interactions that enable both physical and emotional care of people living with dementia in hospital. Future research needs to identify how such changes can be implemented, and how they can be maintained in the long term. To do this, well-designed controlled studies with improved reporting of methods and intervention details to elevate the quality of available evidence and facilitate comparisons across different interventions are required. Study registration: This study is registered as PROSPERO CRD42018086013. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 43. See the NIHR Journals Library website for further project information. Additional funding was provided by the NIHR Collaboration for Leadership in Applied Health Research and Care South West Peninsula.